Meta-Analysis of Social Networking Sites for the Purpose of Preventing Privacy Threats in the Digital Age - Alvarez, Teresa; Chen, Hsieh-Chih (Bright Publisher, 2021)
This article will discuss the challenges to privacy and data mining in social networking sites (Social Networking Sites). The author begins by defining privacy and data mining in today's big data sector before doing a meta-synthesis analysis. Numerous references and literature reviews were undertaken in order to compile material pertinent to the topic of privacy risks and data mining on social networking sites. According to the researchers' conceptualization, privacy concerns and data mining on SNS can be classified into three categories: multimedia content threats, traditional threats, and social threats. Each category is subdivided into multiple threat types. The author notes that in addition to utilizing the privacy measures offered by the SNS site, users must develop an early understanding of the difference between information and secrets. Users must use caution when deciding what content to share on social media platforms and what not to share.